Shadows and spirals in the protoplanetary disk HD 100453 - Benisty, Monique; Dullemond, Cornelis (Astronomy and astrophysics, 2016)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics